Gender-based violence in a complex humanitarian context: Unpacking the human sufferings among stateless Rohingya women. (April 2022) - Priddy, Grace; Doman, Zoe; Berry, Emily; Ahmed, Saleh
Rohingya is one of the ethnic minority groups that has faced profound ethnic violence against them in their home country, Myanmar. Almost a million Rohingya have fled to Bangladesh and are currently living in extremely precarious conditions near the Myanmar–Bangladesh border. Despite the sufferings and oppressions of all Rohingya, women, in particular, have been victims of sexual violence. Using various information sources, this paper analyzes different dimensions of the gender-based violence that has endured in Myanmar for decades. This paper also highlights the health and wellness of Rohingya women, including impacts made during the COVID-19 pandemic. Furthermore, it provides a framework for reducing gender-based violence in the Rohingya camps in Bangladesh. Even though this paper focuses on the Rohingya crisis, insights are relevant to other contexts facing similar social, political, and humanitarian crises, particularly in the Global South.